Pengaruh Desain Kemasan Terhadap Pembelian Impulsif yang Dimediasi Emosi Positif - Widya Nur Fauziyah; Lia Siti Julaeha (Jurnal Ilmiah Wahana Pendidikan, 2022)
Entering the current era, which is growing rapidly, many cultures have entered, one of which is Korean culture. In this case, culture and anything that smells of Korea quickly becomes a trend. Super Junior is a boy band that has been named the "King of Halluyu Wave," which, in March 2021, celebrates its togetherness in 15 years by releasing 13 album versions. -Pop who will buy everything Korean without thinking just because it has unique packaging, different themes, and photo styles regardless of the quality and price of the goods is called impulse buying. Where K-pop fans make these purchases because they feel enthusiastic and happy, this study was conducted to examine the effect of packaging design on impulse buying mediated by positive emotions on the Super Junior The Renaissance album. This type of research uses quantitative methods with a descriptive approach, multiple linear analysis, and path analysis (because it uses mediating variables). Researchers used a sample of 125 respondents obtained by distributing questionnaires using a Likert scale as primary data. The results in this study show several influences, including (1) Packaging Design affects Positive Emotions, (2) Packaging Design has an effect on Impulsive Purchases, (3) Positive Emotions have an effect on Impulsive Purchases, and (4) Positive Emotions cannot mediate Packaging Design on Impulsive Purchases. Contribution to business pioneers as a useful ingredient in making products so that they have a great focus on product packaging design